The cyclicality of effective wages within employer-employee matches in a rigid labor market - Silke Anger (Institute for the Study of Labor (IZA), 2011)
This study analyzes real wage cyclicality for male full-time workers within employer-employee matches in Germany over the period 1984-2004. Five different wage measures are compared: the standard hourly wage rate; hourly wage earnings including overtime and bonus pay; the effective wage, which takes into account unpaid overtime; and monthly earnings, with and without additional pay. None of the hourly wage measures exhibits cyclicality except for the group of salaried workers with unpaid overtime. Their effective wages show a strongly procyclical reaction to changes in unemployment. Despite acyclical wage rates, salaried workers without unpaid overtime experienced procyclical earnings movements if they had income from extra pay. Monthly earnings were also procyclical for hourly paid workers with overtime pay. These findings suggest that cyclical earnings movements are generated by variable pay components, such as bonuses and overtime, and by flexible working hours. The degree of earnings procyclicality revealed for the German labor market is comparable to the United States.
urn:nbn:de:101:1-201104113620
Keywords: E32; J31; 330; real wage cyclicality; effective wages; unpaid overtime; bonus payments; firm stayers; Reallohn; Lohndrift; Konjunktur; Betriebszugehörigkeit; Arbeitsmarktflexibilität; Schätzung; Deutschland